Penyutradaraan Video Feature “Kabaret Bandung: Seni Berbicara, Bahasa Berkarya” dengan Penerapan Gaya Eksposisi - Moch Fadly Renaldi Arifin; Santi Susanti; Teddy Kurnia Wirakusumah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This final project is a video feature focusing on cabaret as a platform for developing language and artistic expression among its members. The video presents several interviewees as the primary content, offering insights into their experiences. In its creation, the directing process plays a crucial and inseparable role. This video feature applies a directing concept that significantly influences the production process, resulting in a well-structured piece. In general, directing is the process of translating a script into a visual form that aligns with the creative vision. The purpose of this report is to explain the directing concept applied in the making of the video, covering the video feature style, the chosen approach, and the structure of its presentation. The director holds a central role in overseeing all stages of production—pre-production, production, and post-production. The directing style used in this video adopts an expository approach, aiming to convey the story and message through voice-over narration and interviews with key sources. The video feature “Kabaret Bandung: The Art of Speaking, the Language of Creation” successfully implements key directing principles, both in terms of style and approach. The application of these concepts allows the video to be crafted in line with the director's vision and the intended target audience.